The correlation between intrinsic and extrinsic motivation and the employee's performance in SME Malaysia - Ivus, Chan Jiong; Loh, Wen Feng; Wong, Sze Xian; Yap, Pei Chin (2023)
Enhancing employee performance within Malaysian small and medium-sized enterprises (SMEs) can be achieved by harnessing the versatility of both extrinsic and intrinsic motivation as effective tools. In the aftermath of the Covid-19 pandemic, there has been a surge in the requirement for heightened employee performance across diverse global industries. The profound ramifications of the Covid-19 outbreak have been unmistakable. In this context, both extrinsic and intrinsic motivation have demonstrated their potential in elevating employee performance. Evidently, the adept management of employee motivation significantly contributes to the success of SMEs in Malaysia. The significance of both extrinsic and intrinsic motivation in shaping the performance of SMEs employees has been duly acknowledged and established as the primary objective of the present research. The main aim of this research is to investigate the potential correlation among the four variables which include Recognition (Recog), Autonomy (Auto), Compensation (Compen), and Company Policy (Compoli) will have the correlation with the performance of employees in Malaysian SMEs. The research was carried out, involving the distribution of questionnaires to 268 respondents across four chosen states include Selangor, Kuala Lumpur, Johor, and Perak. A total of 268 responses were successfully collected. The research model underwent testing through Reliability and Multiple Linear Regression analyses. The result reveal that Recog, Auto, Compen, and Compoli exhibit a notable and significant impact on employee performance within SMEs. Furthermore, this research offers valuable insights for SMEs and future research endeavours seeking to comprehend the correlation between extrinsic and intrinsic motivation and the performance of employees in Malaysian SMEs. Additionally, a set of recommendations is outlined to guide upcoming research efforts, thereby reinforcing the rationale for further exploration in areas of potential enhancement.